2020
DOI: 10.3390/genes11050492
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes of Natural Killer Cells Can Distinguish Rheumatoid Arthritis Patients from Healthy Controls

Abstract: Rheumatoid arthritis (RA) is one of the most prevalent autoimmune diseases, while its molecular triggers are not fully understood. A few studies have shown that natural killer (NK) cells may play either a pathogenic or a protective role in RA. In this study, we sought to explore NK cell markers that could be plausibly used in evaluating the differences among healthy controls and RA patients. Publicly available transcriptome datasets from RA patients and healthy volunteers were analyzed, in order to identify di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Despite their increased ratios in inflamed synovium, NK cells have been shown to be decreased in peripheral blood samples of RA patients when compared with that of healthy subjects ( 265 , 266 ). Additionally, it has been demonstrated in a study that activated NK cells were decreased in peripheral blood of RA patients compared to healthy subjects whereas the frequency of resting NK cells was not altered ( 267 ). These findings suggest that activated NK cells might be infiltrated to the inflamed synovium of RA patients.…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…Despite their increased ratios in inflamed synovium, NK cells have been shown to be decreased in peripheral blood samples of RA patients when compared with that of healthy subjects ( 265 , 266 ). Additionally, it has been demonstrated in a study that activated NK cells were decreased in peripheral blood of RA patients compared to healthy subjects whereas the frequency of resting NK cells was not altered ( 267 ). These findings suggest that activated NK cells might be infiltrated to the inflamed synovium of RA patients.…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…Another study identified differentially expressed genes in NK cells obtained from RA patients versus healthy controls. NK cells isolated from patients with RA expressed higher mRNA levels of CD56, CXCL16, PECAM-1, ITGB7, BTK, TLR10, and IL-1β, but lower levels of CCL2, CCR4, RELA and IBTK [ 57 ]. Yamin et al.…”
Section: The Role Of Nk Cells In Ramentioning
confidence: 99%
“…Single-nucleotide polymorphisms in NK cell-related genesespecially NKG2D and MHC class I polypeptide-related sequence A (MICA)-were shown to be associated with RA susceptibility and severity (104)(105)(106)(107). Early studies reported conflicting findings regarding the roles of NK cells in RA, which may be attributable to the fact that peripheral but not local synovial NK cells were examined; moreover, the different NK subsets were not distinguished, and the data were derived from different cohorts (108)(109)(110).…”
Section: Nk Cells and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%